Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Karakter Pada Mata Pelajaran Kimia SMA - Eka Sari; Syamsurizal Syamsurizal; Asrial Asrial (Universitas Jambi, 2016)
The purpose of this study is to create students’ worksheet based on character values. This is an R & D research with model ADDIE instructional design model (analysis, design, development, implementation, and evaluation). The feasibility of worksheet was examined using a questionnaire. Based on the questionnaire results validity tested by the experts, the worksheet was declared to be valid and it is applicable to be used and tested, whereas the response of the teachers and students about the worksheet, it stated that the worksheet categorized as a very good one. Meanwhile the data of character development and students’ skill on doing practical work that gained from the observation sheet. The results of the responses of teachers and students to worksheet in the criteria very good so it has good quality on student interest. While the results of the analysis of observation sheets scientific attitude and skills of students in conducting lab has a good criteria. Keyword: Based Worksheet, Chemistry, Senior High School.